2001
DOI: 10.1002/jnr.10040
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum, NO, and nerve growth factor neurotoxicity in cholinergic neurons

Abstract: Several neurotoxic compounds, including Al, NO, and beta-amyloid may contribute to the impairment or loss of brain cholinergic neurons in the course of various neurodegenerative diseases. Genotype and phenotypic modifications of cholinergic neurons may determine their variable functional competency and susceptibility to reported neurotoxic insults. Hybrid, immortalized SN56 cholinergic cells from mouse septum may serve as a model for in vitro cholinotoxicity studies. Differentiation by various combinations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 77 publications
4
32
0
Order By: Relevance
“…The SI effect on learning and memory ability of chronically Al exposed animals might be related to their antioxidative function. Considerable evidence has demonstrated that chronic Al exposure caused the dysfunction of several neurotransmitter enzymes, including choline acetyl transferase (ChAT), acetylcholinesterase (AChE) (Bielarczyk et al, 1998;Szutowicz, 2001) and glutamate α-decarboxylase (Nayak and Chatterjee, 2001). Al exposure also altered the concentrations of amino acid neurotransmitters, their metabolites in several brain regions (Beal et al, 1989;Jia et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The SI effect on learning and memory ability of chronically Al exposed animals might be related to their antioxidative function. Considerable evidence has demonstrated that chronic Al exposure caused the dysfunction of several neurotransmitter enzymes, including choline acetyl transferase (ChAT), acetylcholinesterase (AChE) (Bielarczyk et al, 1998;Szutowicz, 2001) and glutamate α-decarboxylase (Nayak and Chatterjee, 2001). Al exposure also altered the concentrations of amino acid neurotransmitters, their metabolites in several brain regions (Beal et al, 1989;Jia et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They include: Aβ 1–42 accumulation, excitotoxicity/NO excess, mitochondrial dysfunction, hypoxia/anoxia/hypoglycaemia, oxygen radicals formation, inflammation, metals (Ca 2+ , Zn 2+ , Fe 2+ , Al 3+ ) accumulation, or neurothrophin depletion, which were investigated as cytotoxic signals in AD (Fig. 2) [27, 90, 91, 93, 94, 112–118]. Also activation of microglia yielding increased release of proinflamatory interleukins may induce neurodegeneration through Wnt or p75 neurotrophin receptor-dependent signal transduction pathways [75, 119, 120].…”
Section: Early and Late Mechanisms Of Energy And Acetyl-coa-dependentmentioning
confidence: 99%
“…Most of these cytotoxic signals directly affected activities of enzymes linked with energy and acetyl-CoA metabolism in humans as well as animal and cellular models of AD [13, 27, 96, 102, 104, 118]. …”
Section: Early and Late Mechanisms Of Energy And Acetyl-coa-dependentmentioning
confidence: 99%
“…Selective lost of cholinergic [86], GABAergic [246] and nitroxidergic [247] neurons in response to exposure to aluminium has been reported. Furthermore, alteration of nerve cell morphology is a common feature of aluminium neurotoxicity.…”
Section: Synaptic Strengthmentioning
confidence: 99%